Mango de azúcar (Mangifera indica), variedad de Colombia : características antioxidantes, nutricionales y sensoriales (2014)
ABSTRACT: The sugar mango is a small Colombian cultivar with low fiber content, good aroma and flavor. This research evaluated antioxidant capacity (FRAP, DPPH) of the fruit at different ripening stages classified by visual inspection and CIELab scale. Nutritional and sensory characteristics and ORAC value were measured in the ripe fruit. Sensorial characteristics of two mango nectars sweetened with sucrose and sucralose using ripe fruit were determined by affective acceptance test and Hedonic scale. Results showed that classification by visual inspection coincided with the CIELab scale for all ripening stages. The green mango has 45% more flavonoids than the mature one. The carotenoid content, DPPH and FRAP values were similar in the different ripening stages. Sucralose sweetened nectar was accepted by 94.9% compared with that sweetened with sucrose (89.1%). Results indicate that mango sugar fruit and nectar present antioxidant capacity, bioactive and nutritional compounds with potential health benefits.